Effects of biodegradation, biotoxicity and microbial community on biostimulation of sulfolane. (April 2023) - Chang, Shao-Heng; Lin, Chi-Wen; Cheng, Yu-Shen; Liu, Shu-Hui
Abstract: To evaluate the effectiveness of biostimulation in remediating soil-free groundwater and groundwater with soil, experiments were conducted using soil and groundwater samples that were contaminated with sulfolane. The main objective was to characterize the differences in sulfolane removal efficiency and biotoxicity between in situ soil-free groundwater and groundwater with soil and different concentrations of dissolved oxygen (1 mg/L and 5 mg/L) and various nutrient salts ( in situ and spiked). Optimizing the nutrient salt conditions improved the removal efficiency of sulfolane by 1.8–6.5 that under in situ nutrient salt conditions. Controlling the dissolved oxygen concentration enhanced the efficiency of removal of sulfolane by 1.5–4.5 times over that at the simulated in situ dissolved oxygen concentration, suggesting that the degradation of sulfolane by indigenous microorganisms requires nutrient salts more than it requires dissolved oxygen. Biotoxicity data showed that the luminescence inhibition of Aliivibrio fischeri by sulfolane was lower in the biostimulated samples than in the pre-treated samples. Biostimulation reduced the biotoxicity of the treated samples by 42−51%, revealing that it was effective in removing sulfolane and reducing biotoxicity. Microbial community analysis showed that the biostimulation did not change the dominant species in the original in situ community, and increased the proportion of sulfolane-degraders. The outcome of this study can be used to set parameters for the remediation of groundwater that is contaminated by sulfolane in oil refineries. Graphical abstract: Image 1 Highlights: Biostimulation reduced toxicity of groundwater contaminated with sulfolane. Difference in biostimulation efficacy of contaminated soil and water was assessed. Sulfolane biodegradation requires nutrient salts more than dissolved oxygen. Biostimulation retains the bacterial function and biodiversity of native microbes.